Surgical treatment of tumours of the sternum – 10 years’ experience - Kozak, Katarzyna; Łochowski, Mariusz; Białas, Adam; Rusinek, Michał; Kozak, Józef (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Introduction: Tumours of the sternum are rare and can be malignant, benign or inflammatory. Aim: To determine the clinical, pathological and therapeutic options for tumours of the sternum. Material and methods : We report a series of 30 cases of sternal tumours treated in our institution in the period 2006–2015. There were 10 malignant tumours located in the body of the sternum, 2 in the manubrium (metastases of kidney and thyroid carcinoma) and 18 benign tumours located in different parts of the sternum. Diagnosis was obtained by computed tomography scan of the chest, surgical biopsy or excision of the tumours. Results: Malignant tumours were excised radically. Reconstruction of the sternum was obtained by allogenic mesh (polypropylene) and local tissues (mainly pectoralis major muscle). There was 1 postoperative cardiac death. Patients with malignancy were referred for adjuvant chemoradiotherapy. After 2 years there were 4 cases of recurrence of chondrosarcoma (1 case of local recurrence and 3 cases of pulmonary metastases). Recurrence of other tumors were not observed. Conclusions: The management of sternal tumours is dependent on the histological type and the possibility of surgical excision. Reconstruction of the chest wall can be achieved by autogenic or allogenic materials.